IMPLEMENTASI TEKNOLOGI DIGITAL DALAM PENYUSUNAN RENCANA KERJA SEKOLAH: SYSTEMATIC LITERATURE REVIEW - Atsauri, Muhammad Sofyan; Sukarman, Sukarman; Kurniawan, Muhammad Aris (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study synthesizes scholarly evidence on the implementation of digital technologies in the preparation of School Work Plans (Rencana Kerja Sekolah/RKS) as strategic and operational planning instruments that guide programmes, budgeting, and school performance monitoring. Although information systems, data dashboards, and collaborative platforms are increasingly adopted in educational administration, knowledge about how these technologies enhance the quality of school planning remains fragmented. A Systematic Literature Review (SLR) was conducted following PRISMA 2020. Literature was searched in Scopus, Web of Science, ERIC, and ScienceDirect/Google Scholar using keywords related to school development plan, school improvement planning, management information system, dashboard, and digital budgeting (2015–2025). After de-duplication, title/abstract screening, full-text assessment, and Quality Assessment (QA1–QA3), 15 studies were retained and analysed via thematic synthesis. Findings indicate five dominant technology clusters: (1) data infrastructures (EMIS/SMIS/SIS) for needs diagnosis and priority mapping; (2) analytics and dashboards for sense-making and target setting; (3) digital collaboration platforms that expand stakeholder participation in programme design; (4) e-budgeting/e-procurement systems that strengthen budgeting accountability; and (5) indicator-based monitoring and evaluation systems that accelerate reporting and feedback loops. Successful implementation depends on data literacy, digital leadership, technical support, data governance, and change management. This review proposes a 'Digital Data-Enabled RKS Cycle' to guide technology integration across the entire school planning process. ABSTRAK Penelitian ini mensintesis bukti ilmiah tentang implementasi teknologi digital dalam penyusunan Rencana Kerja Sekolah (RKS) sebagai instrumen perencanaan strategis dan operasional yang memandu program, penganggaran, serta pemantauan kinerja sekolah. Walaupun adopsi sistem informasi, data dashboard, dan platform kolaborasi meningkat pada administrasi pendidikan, pengetahuan mengenai bagaimana teknologi tersebut meningkatkan kualitas perencanaan sekolah masih tersebar. Kajian ini menggunakan metode Systematic Literature Review (SLR) dengan pedoman PRISMA 2020. Pencarian literatur dilakukan pada Scopus, Web of Science, ERIC, dan ScienceDirect/Google Scholar menggunakan kata kunci terkait school development plan, school improvement planning, management information system, dashboard, dan digital budgeting pada rentang 2015–2025. Setelah penghapusan duplikasi, penyaringan judul atau abstrak, penilaian teks penuh, serta Quality Assessment (QA1–QA3), terpilih 15 studi yang dianalisis melalui sintesis tematik. Hasil menunjukkan lima kelompok teknologi dominan: (1) infrastruktur data (EMIS/SMIS/SIS) untuk diagnosis kebutuhan dan pemetaan prioritas; (2) analitik dan dashboard untuk sense-making dan penetapan target; (3) platform kolaborasi digital yang memperluas partisipasi pemangku kepentingan dalam penyusunan program; (4) sistem e-budgeting atau e-procurement yang meningkatkan akuntabilitas penganggaran; serta (5) sistem monitoring dan evaluasi berbasis indikator yang mempercepat pelaporan dan umpan balik. Keberhasilan implementasi ditentukan oleh literasi data, kepemimpinan digital, dukungan teknis, tata kelola data, dan manajemen perubahan. Penelitian ini merekomendasikan kerangka 'Siklus RKS Berbasis Data Digital' sebagai panduan integrasi teknologi pada seluruh tahapan perencanaan sekolah.